2022
DOI: 10.3389/fimmu.2022.809285
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Type-, Age- and Past Infection-Dependence of the Humoral Response to SARS-CoV-2 Spike S Protein

Abstract: The emergence of COVID-19 has led to a worldwide challenge for the rapid development of vaccines. Several types of safe and effective vaccines have been available in a time frame never seen before. Now that several hundred million people have been vaccinated there is an opportunity to compare vaccines in terms of protection and immune response. Here, we have applied a highly sensitive multiplexed flow cytometry method to measure simultaneously IgM, IgG1 and IgA anti-spike protein antibodies generated in respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…The immunogenicity of the different vaccines upon completion of primary vaccination was compared in the population. This analysis revealed that both seroconversion rates and the levels of IgG reactive to Spike and S1 RBD were higher on those participants vaccinated with BNT16b2, followed by ChAdOx1 and CoronaVac, in agreement with other studies (Barin et al 2022;Romero-Pinedo et al 2022). Quite remarkably, the seroconversion rates for Spike binding antibodies determined in our study (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The immunogenicity of the different vaccines upon completion of primary vaccination was compared in the population. This analysis revealed that both seroconversion rates and the levels of IgG reactive to Spike and S1 RBD were higher on those participants vaccinated with BNT16b2, followed by ChAdOx1 and CoronaVac, in agreement with other studies (Barin et al 2022;Romero-Pinedo et al 2022). Quite remarkably, the seroconversion rates for Spike binding antibodies determined in our study (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…This analysis revealed that both seroconversion rates and the levels of IgG reactive to Spike and S1 RBD were higher on those participants vaccinated with BNT16b2, followed by ChAdOx1 and CoronaVac, in agreement with other studies (Barin et al . 2022; Romero-Pinedo et al . 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While mucosal immunization would induce SIgA antibodies, parenteral doses would improve systemic response [48][49][50]. Data from rodents showed that nasal immunization enhanced IgA in sera [46] and both sera and respiratory mucosa [47]. However, there is little evidence from human studies.…”
Section: Secretory Iga: the Mucosal Weaponmentioning
confidence: 99%
“…Current SARS‐CoV‐2 vaccines can also induce IgA, as it has been verified for the mRNA vaccines from Moderna (mRNA1273) and Pfizer/BioNTech (BNT162b2) and the viral vector vaccine from Oxford/Astrazeneca (ChAdOx1) [47].…”
Section: Immunological Defence On Mucosal Surfacesmentioning
confidence: 99%
See 1 more Smart Citation